Error Analysis of Aspect Particle "Le" for Zimbabwean Students at University of Zimbabwe - Yun Sha, Mao; Mumbijo, Yeukai (Eximia, 2022)
Studying Chinese grammar is not an easy road for a lot of foreign students. Chinese auxiliary "Le" undoubtedly serve as the main point and the difficult point in teaching Chinese as second language, so far, students who are becoming interested in studying the Chinese auxiliary "Le" are innumerable. Chinese auxiliary "Le" is rich in semantic meanings, its position is flexible and its pragmatic is very complex, making it hard for foreigners learning Chinese to master. Zimbabwean students at the University of Zimbabwe are facing challenges when learning auxiliary "le". Many scholars from different countries have written many articles trying to address this issue as it has been affecting students from different nationalities, There are reports which shows that there were improvements to some extent in areas where this issue was addressed; but still a number of Zimbabwean students have challenges in mastering the concept of using the auxiliary "le” this article is written to try and assess errors made by students when using auxiliary "le" as well as provide possible solutions which help teachers when teaching Zimbabwean students. This thesis approaches this issue from a different angle through compiling data on common biased errors such as the local language interference phenomenon, grammatical rules in the Chinese language, teaching materials and environment, students' lack of proficiency, the complex nature of the Chinese auxiliary "le" since it doesn't have one use in Chinese language, overuse of the auxiliary "le" by Zimbabwean students and lastly, wrong word arrangement when constructing a sentence with auxiliary "le". This report conducted a statistical analysis with 3 groups of students. First group of students were students who had just studied Chinese language for 3 months. The beginners were only 15 students. The second group of students were the intermediate students. Their level of Chinese is better than the beginners and they have studied Chinese for more than a year. The intermediate students were 15 students. The last group of students who I analyzed were the advanced students who were coming to China for a year program of studying Chinese language. On the grounds of analysis, this report tries to find common errors in each group of students and common errors in all groups. This article also tries to find the reasons to these errors as well as providing solutions to these errors. This is all for the betterment of learning Chinese language in Zimbabwe.